PERAN ETIKA PROFESI DALAM MENGATASI TANTANGAN TUGAS PENYELIA HALAL DI INDUSTRI HALAL DI INDONESIA - Cahyani, Putri Tri; Kania, Dede; Anwar, Syahrul; Fitriyani, Fitriyani (Universitas Mathla’ul Anwar Banten, 2025)
This study aims to analyze the challenges faced by halal supervisors in Indonesia and examine the role of professional ethics in addressing these challenges. The study employs a qualitative approach with a literature review method, gathering data from various sources such as scholarly journals, books, and official documents. The analysis is conducted descriptively and analytically to understand the relevance of professional ethics in supporting the duties of halal supervisors. The findings indicate that the application of professional ethics, which includes values such as honesty (shiddiq), trustworthiness (amanah), professionalism (fathanah), and sincerity, serves as a primary solution in overcoming various challenges faced by halal supervisors in Indonesia's halal industry. These ethical principles not only preserve the integrity of halal supervisors but also provide concrete guidance in addressing moral dilemmas, such as pressures to relax halal standards and conflicts of interest. The ethical values outlined in SKKNI No. 215 of 2016, such as accuracy, precision, independence, and objectivity, assist halal supervisors in performing their duties to high standards, ensuring product halalness, and maintaining transparency in decision-making. While technical training is important, this study emphasizes the need for training programs that integrate the strengthening of ethical values and real-case simulations to prepare halal supervisors for more complex challenges. Thus, professional ethics plays a strategic role not only in supporting the execution of halal supervisors' duties but also in reinforcing public trust in halal products in Indonesia.